Dynamical aspects of nanoparticle formation by wire explosion process. (10th June 2020) - Ranjan, P; Nguyen, D H; Chen, L; Cotton, I; Suematsu, H; Chakravarthy, S R; Jayaganthan, R; Sarathi, R
Abstract: Copper nanoparticles (NPs) were produced by wire explosion process (WEP) and it was noted that the amount of energy (E) deposited on the wire and the ambient pressure play a major role on the size of particles formed. Dynamic diffusion and condensation processes of NPs formation by WEP were modelled. Calculations of critical size of embryo, activation energy and nucleation rate of the formation of NPs in WEP were made considering classical homogeneous nucleation theory. Decrease in critical size of nuclei and activation energy, increase in nucleation rate with high E (540 J) and low operating pressure (10 kPa) confirm the formation of small size NPs (26 nm). Different cooling rates due to unsymmetrical shape of the vapour cloud has been identified as the cause for generating mixed particle sizes. The qualitative analysis conducted in this work validates the obtained experimental results and can be used as a design tool for industrial apparatus to produce NPs in bulk.